Oral History and digital tools: new possibilities in working with orality - Victorasso, Pedro Henrique [UNESP]; de Oliveira, Eduardo Romero [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2024)
This paper aims to investigate what has advanced in the debate on the oral history between 2000 and 2020 in literary productions (scientific papers) in the Google Scholar database related mainly to methodological issues. Therefore, we believe that using a bibliometric analysis tool would be more suitable for this investigation. Therefore, we chose to conduct research using the program Harzing’s Publish or Perish, a program that retrieves and analyzes academic citations. Finally, we seek to understand how the use of the digital tool Nvivo can impact the work with oral sources and if this can bring new questions to the research of oral history. Thus, we reflect on the potential of Digital Humanities as a possibility to advance the debate on social narratives from the past.
HISTÓRIA ORAL E FERRAMENTAS DIGITAIS: NOVAS POSSIBILIDADES NO TRABALHO COM A ORALIDADE
Keywords: Nvivo; Oral History; Software